1997
DOI: 10.1093/emboj/16.13.4060
|View full text |Cite
|
Sign up to set email alerts
|

The plant defense response to cucumber mosaic virus in cowpea is elicited by the viral polymerase gene and affects virus accumulation in single cells

Abstract: Resistance to infection in cowpea by strains of cucumber mosaic virus (CMV) involves a local, hypersensitive response (HR) and a localization of infection. These responses can be separated by mutation at two sites (nucleotides 1978 and 2007, in codons 631 and 641) in the CMV 2a polymerase gene. Changes to both sites of a restricted strain allow systemic infection without an HR and increase the accumulation of both the 2a protein and viral RNA in protoplasts, while changing position 1978 alone results in a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 57 publications
5
64
0
Order By: Relevance
“…Finally, a role for posttranslational modification in 2a protein recognition, by RT4-4, came from the finding that the CMV 2a phosphorylation mimic mutant failed to elicit the necrosis phenotype (37). Together, these findings are consistent with results of previous studies that identified the 2a protein as the elicitor of a CMV defense response in cowpea (22).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, a role for posttranslational modification in 2a protein recognition, by RT4-4, came from the finding that the CMV 2a phosphorylation mimic mutant failed to elicit the necrosis phenotype (37). Together, these findings are consistent with results of previous studies that identified the 2a protein as the elicitor of a CMV defense response in cowpea (22).…”
Section: Discussionsupporting
confidence: 88%
“…In a previous study, Kim and Palukaitis (22) identified amino acid residues 631 (Phe) and 641 (Ala) of the Fny 2a protein as determinants of a CMV-mediated HR in cowpea. To test the hypothesis that these same residues are involved in our observed CMV-mediated necrosis response, the 2a sequences of the eight CMV strains used in the present study were determined.…”
Section: A Motif Is Necessary For the Necrosis Responsementioning
confidence: 99%
“…It is normally believed that, in the incompatible response, HR is activated by the R-AVR interaction, which restricts pathogen ingress, whereas compatibility triggered cell death may facilitate pathogen infection (Kim and Palukaitis, 1997;Greenberg et al, 2000). By contrast, several studies indicate that cell death and the prevention of pathogen invasion likely have separable functions in disease resistance (Bendahmane et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria and fungi introduce diverse mutations into their Avr genes, including point mutations, insertions, and even deletions (3,34,47,60,65). However, due to multifunctionality of viral genes, minor modification of Avr genes is the only affordable mechanism of evasion by plant viruses (7,16,26,40,41,50,53,66). Thus, in a plant genotype harboring an R gene against a plant virus, the elicitation of R-mediated defense responses is dependent upon the elicitor function of the invading virus.…”
mentioning
confidence: 99%